HUMAN CHARACTERISTICS THROUGH PHYTONYMS AND ZOONYMS IN THE PHRASES OF DIFFERENT SYSTEMIC LANGUAGES - Jurakulov Abror Raufovich (Galaxy International Interdisciplinary Research Journal, 2024)
People has been interested in the natural world since ancient times, and along with getting into the secrets of the world, they tried to study the world around them in order to understand their place in it. Undoubtedly, man’s understanding of the universe began with the study of domesticated animals and those hunted in the wild. All ideas, thoughts and opinions about animals have been formed for millennia. These religious and mythical views served as the basis for scientific knowledge of the flora and fauna. With this, they tried to illuminate the dual nature of humans, their difference from animals and their place in the structure of the universe.